Pertanggungjawaban Pemilik Kos Terhadap Wanprestasi Yang Dilakukan Dari Perjanjian Sewa Menyewa Secara Lisan - Nadia A Isyah Fatmawati (JOURNAL SAINS STUDENT RESEARCH, 2023)
Agreement is a very common process in human life. The agreement that often occurs is a rental agreement, such as a boarding room rental agreement. This agreement was carried out in order to fulfill the basic needs of humans who need a place to live. In practice, the agreement is often made verbally. The verbal agreement to rent a boarding room is valid as long as it meets the conditions for the validity of the agreement in article 1320 of the Civil Code. The rental agreement for a boarding room which is executed verbally by both parties gives rise to an agreement which gives rise to rights and obligations for both parties. However, what if after the agreement is executed, the boarding house owner defaults in that the facilities provided by the boarding house are not in accordance with what has been agreed. What form of accountability can be imposed on boarding house owners who default by not providing facilities in accordance with what has been agreed upon by both parties? This makes the boarding house renter suffer a loss and is entitled to claim his rights according to what was agreed or receive appropriate compensation.